2018
DOI: 10.1214/18-ejp177
|View full text |Cite
|
Sign up to set email alerts
|

Non-equilibrium steady states for networks of oscillators

Abstract: Non-equilibrium steady states for chains of oscillators (masses) connected by harmonic and anharmonic springs and interacting with heat baths at different temperatures have been the subject of several studies. In this paper, we show how some of the results extend to more complicated networks. We establish the existence and uniqueness of the non-equilibrium steady state, and show that the system converges to it at an exponential rate. The arguments are based on controllability and conditions on the potentials a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Note that the MZ equation ( 4) and its projected form (5) for stochastic systems have the same structure as the classical MZ equations for deterministic (autonomous) systems [45,42,44]. However, the Liouville operator L is now replaced by the Kolmogorov operator K. Let us consider the weighted Hilbert space…”
Section: Mori-type Generalized Langevin Equations For Sdesmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the MZ equation ( 4) and its projected form (5) for stochastic systems have the same structure as the classical MZ equations for deterministic (autonomous) systems [45,42,44]. However, the Liouville operator L is now replaced by the Kolmogorov operator K. Let us consider the weighted Hilbert space…”
Section: Mori-type Generalized Langevin Equations For Sdesmentioning
confidence: 99%
“…where K * is the L 2 (M )-adjoint operator of K. Throughout the paper, we further assume that ρ is a smooth function which decays to 0 when approaching boundary ∂M . For frequently used statistical physics models, these two assumptions are generally hard to prove since it involves the analysis of the degenerate elliptic operator K. Some recent studies on hypoellipticity [5,7] have shown the possibility to obtain affirmative answers using the rather complicated Hörmander analysis. These theoretical results, together with numerical studies such as [22,23], suggest that the uniqueness, smoothness and the decaying properties of ρ at ∂M are rather technical assumptions.…”
Section: Generalized Fluctuation-dissipation Theoremmentioning
confidence: 99%
“…/ norm was constructed in which the dynamics contracts. Although structurally different but similar in spirit, we refer the reader to the papers [4,11,13] and the references therein for scenarios where Langevin dynamics produces subgeometric rates of convergence either due to absence of friction on certain particles or weak Poincaré inequalities being satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the existence, uniqueness of a non-equilibrium stationary state and exponential convergence towards it in more complicated networks of oscillators (multi-dimensional cases) see [12]. The proofs there are inspired by the above-mentioned works in the 1-dimensional chains.…”
Section: State Of the Artmentioning
confidence: 99%